2011
DOI: 10.1590/s1516-44462011005000015
|View full text |Cite
|
Sign up to set email alerts
|

Reliability study of the Behavioral Assessment of the Dysexecutive Syndrome adapted for a Brazilian sample of older-adult controls and probable early Alzheimer's disease patients

Abstract: Objective: Ecological tests are useful in assessing executive function deficits and may be of value in appraising response to treatment in Alzheimer's disease patients. Our aims were to examine executive function using the Behavioral Assessment of the Dysexecutive Syndrome for a Brazilian sample of older-adult controls and probable early Alzheimer's disease patients, and verify the applicability of this test battery. Method: Forty-one older-adult controls were matched with mild Alzheimer's disease patients by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
2
0
4
Order By: Relevance
“…Relativamente à validade de critério, verificase correlação positiva entre o total BADS e o total da DRS-2 e suas subprovas, com excepção da subprova da Atenção. Essa correlação entre a BADS e medidas genéricas de funcionamento cognitivo já havia sido referida por Canali et al, 19 utilizando o Minimental State Examination. A não existência de uma correlação significativa entre a Atenção da DRS-2 e a BADS pode estar ligada ao facto de alguns dos elementos desta subprova serem na verdade provas de domínio práxico e não tanto de atenção executiva.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Relativamente à validade de critério, verificase correlação positiva entre o total BADS e o total da DRS-2 e suas subprovas, com excepção da subprova da Atenção. Essa correlação entre a BADS e medidas genéricas de funcionamento cognitivo já havia sido referida por Canali et al, 19 utilizando o Minimental State Examination. A não existência de uma correlação significativa entre a Atenção da DRS-2 e a BADS pode estar ligada ao facto de alguns dos elementos desta subprova serem na verdade provas de domínio práxico e não tanto de atenção executiva.…”
Section: Resultsunclassified
“…Para o total da bateria, determinou-se um valor de sensibilidade de 100% e de especificidade de 73% para um ponto de corte de 6. 19 Esta observação poderá estar ligada ao facto de esta prova ter apresentado efeito de piso nulo nos dois grupos ou, em complemento, à menor amplitude de desempenho possível desta tarefa. A análise da área sob a curva revela boa capacidade discriminativa da BADS e de suas provas.…”
Section: Análise Estatísticaunclassified
See 1 more Smart Citation
“…A BADS também se mostrou sensível para discriminar diferenças no desempenho entre DA e CCL (Armentano, Porto, Brucki, & Nitrini, 2009). O terceiro avaliou idosos saudáveis e pacientes com DA em um estudo de confiabilidade da BADS, que se mostrou eficaz na detecção dos déficits em FE entre os pacientes, especialmente nas tarefas de alternância, monitoramento de tempo e subtestes de mudanças de regras (Canali, Brucki, Bertolucci, & Bueno, 2011).…”
Section: Discussionunclassified
“…23 The aim of the present study was to compare performance on the BADS by patients with aMCI, mild AD, and healthy controls, and to verify the accuracy of the battery for differentiating among the groups. A recent reliability study carried out in Brazil confirmed the effectiveness of the battery for detecting executive function deficits in mild AD.…”
mentioning
confidence: 99%